Strategi Marketing Public Relation untuk Mempromosikan PT. Citilink Indonesia - Feby Mayola; Ade Budi Santoso (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
PT. Citilink Indonesia is a low-cost airline operating in both domestic and international markets. This study explores how the company utilizes Marketing Public Relations (MPR) strategies to promote its brand and services. The focus of this research is on the implementation of integrated marketing communication strategies—particularly through social media and event-based promotions—to build a positive brand image and increase customer loyalty. Previous studies have addressed similar topics, such as PT. KAI’s MPR strategies in digital service transformation and PT. JNE’s efforts to enhance customer satisfaction through MPR. This research employs a descriptive qualitative method, with data collected through interviews and documentation. The findings reveal that Citilink’s MPR strategy adopts the Three Ways Strategy by Thomas L. Harris, which includes push, pull, and pass strategies. These are implemented through social media campaigns on platforms like Instagram, collaborations with Key Opinion Leaders (KOLs), and the organization of educational and entertainment events. The strategy has proven effective in enhancing audience engagement and expanding promotional reach amidst intense competition in the airline industry.